Induction of apoptosis and regression of spontaneous dog melanoma following in vivo application of synthetic cyclin-dependent kinase inhibitor olomoucine - Hajdúch, M; Kolár, Z; Novotný, R; Hanus, J; Mihál, V; Hlobílková, A; Nosková, V; Strnad, M (Anti-cancer drugs, 1997)
This case report describes a dog with spontaneous melanoma of the orofacial region which was treated by a synthetic inhibitor of cyclin-dependent kinases, i.e. olomoucine (OC). The drug was applied i.v. in a single dose of 8 mg/kg/day for 7 days in succession. Repeated bioptic examinations of metastatic cervical lymph nodes showed rapid induction of apoptosis in tumor cells as early as on the third day of treatment. Standard clinical and laboratory examinations did not reveal side effects of the therapy. There were no detectable manifestations of myelosuppression, hepatotoxicity, nephrotoxicity or neurotoxicity. However, transient anemia developed following bleeding from a devitalized tumor mass. For this reason, the dog underwent surgery to minimize tumor load as well as to eliminate the source of bleeding. Two kilograms of primary tumor were extirpated in the course of surgery, including cervical node metastases. Unfortunately, the dog died soon after surgery due to respiratory depression. Histological examinations of the tumor tissue showed marked apoptosis of melanoma cells in both the primary tumor and metastases. The induction of programmed cell death of cancer cells by OC resulted in rapid eradication of at least 68% of the tumor cells. The remaining melanoma cells retained at least equally well in vitro sensitivity to OC as to drugs currently used in clinical practice.
Keywords: Kinetin; apoptóza; psi; Melanoma; Dogs; mužské pohlaví; cyklin-dependentní kinasy; Dog Diseases; inhibitory enzymů; Antineoplastic Agents; Facial Neoplasms; nemoci psů; melanom; protinádorové látky; zvířata; kinetin; nádory obličeje; Purines; Cyclin-Dependent Kinases; puriny; Enzyme Inhibitors; Male; Apoptosis; Animals